Efektivitas Sistem Informasi Akuntansi Lembaga Perkreditan Desa di Kecamatan Kediri - Ida Ayu Nyoman Yuliastuti; I Gede Cahyadi Putra (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to examine and analyze the effect of information technology sophistication, work experience, training and Tri Hita Karana culture on the effectiveness of the accounting information system at the Village Credit Institution (LPD) in Kediri District, Tabanan Regency. The number of LPDs in Kediri District are 21 LPDs with a population of 159 people. The method of determining the sample using purposive sampling method, so as to get a research sample of 105 respondents. The data analysis technique used is multiple linear regression analysis. Of the 105 questionnaires distributed, 81 were filled out and returned. The results of the data analysis showed that the training and culture of Tri Hita Karana had a positive effect on the effectiveness of the accounting information system. It is different with the results on the variables of information technology sophistication and work experience which have no effect on the effectiveness of the accounting information system at the LPD in Kediri District, Tabanan Regency.